PEMBANGUNAN KOTA WISATA BATU DALAM PERSPEKTIF SOSIAL & EKONOMI MASYARAKAT - Agung Suprojo; Budi Siswanto (REFORMASI, 2017)
Abstract : This study aimed to determine the development carried out by Batu in the social and economic perspective of the community. Steps in reaching the welfare of society begin with the creation of vision and mission as a center of agriculture and tourism city. The method used was a descriptive qualitative and an implementation study that concerned on the strengthening of mission and vision of Batu to form a tourism city that led to a situation and condition of its society ‘s functional structure. The results showed that the strengths of Batu vision as an international tourist destination could be strengthened by all components of government, private sectors and community in creating various activities, attractions and types of tourism that could strengthen the social and economic changes of its people. Batu can implement a combination of all resources and potentials it has to be able to develop modern tourism attractions as well as strengthening the local and traditional cultures that attract tourists. From a social perspective, Batu’s development can be sustainable because of the cooperation and the role of government, investors and the community to create interesting tourism concepts. In an economic perspective, the development of Batu is gradually able to change the regional income derived from tourism to be used as much as possible for the prosperity of the people. Keywords: Development, Tourism City, Tourism Attraction, Empowerment, Social Perspective, Economic Perspective Penelitian ini bertujuan untuk mengetahui pembangunan yang dilakukan di Kota Batu dalam perspektif sosial dan ekonomi masyarakat. Langkah dalam menggapai kesejahteraan masyarakat dimulai dengan melahirkan visi dan misi sebagai sentra pertanian dan kota wisata. Metode yang digunakan adalah deskriptif kualitatif dan merupakan studi implementasi yang memperhatikan penguatan visi misi Kota Batu sehingga terbentuk kota wisata yang mengarah pada sebuah situasi maupun kondisi struktur fungsional masyarakatnya. Hasil penelitian menunjukkan bahwa kekuatan visi Kota Batu sebagai destinasi wisata internasional mampu diperkuat oleh seluruh komponen pemerintahan, swasta dan masyarakat dalam melahirkan berbagai kegiatan, wahana maupun jenis wisata yang mampu menguatkan perubahan sosial dan ekonomi masyarakatnya. Kota Batu dapat mengimplementasikan perpaduan dari seluruh sumberdaya dan potensi yang dimilikinya sehingga mampu mengembangkan wahana wisata modern serta penguatan budaya-budaya lokal dan tradisional yang menjadi daya tarik wisatawan. Dari perspektif social, pengembangan Kota Batu dapat berkelanjutan karena terjalin kerjasama dan adanya peranan pemerintah, investor serta masyarakat untuk melahirkan berbagai konsep kepariwisataan yang menarik. Dalam perspektif ekonomi, pengembangan Kota Batu secara bertahap mampu merubah pendapatan daerah yang diperoleh dari kepariwisataan untuk digunakan sebesar-besarnya pada kemakmuran rakyat. Kata Kunci : Pembangunan, Kota Wisata, Wahana Wisata, Pemberdayaan, Perspektif Sosial, Perspektif ekonomi